VESICLES. II. Atopic Dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Diagnosis of atopic dermatitis (AD) is easy when this disorder involves for a long period, with a seasonal chronic-fluctuating course, the classical sites, notably the elbow and knee flexures. Diagnosis can be difficult during the first three months of life and in the presence of lesions complicated by other factors or characterized by an atypical morphology and distribution, i. e. asymmetrical (Fig. 500). (...).